Magnetometry, Acoustical and Inertial Indoor-Positioning in Healthcare - I. V. Cherepanova; I. V. Pospelova; D. S. Bragin; V. N. Serebryakova (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. The problem of localization of moving objects inside buildings becomes more urgent in healthcare. Tracking the movements of patients in real time allows one to provide them with timely medical support in case of sharp deterioration in their vital signs. It is especially important to track the location of patients undergoing a surgery, since the risk of death due to postoperative complications for them is extremely high. Using indoor-positioning technologies in telemedicine systems can solve the problem, thereby reducing the mortality rate of patients and improving the quality of medical care.Aim. To study the applicability of magnetometry, inertial and acoustic technologies for patient’s localization in a hospital.Materials and methods. The analysis of domestic and foreign scientific sources devoted to indoor-positioning based on the above technologies was carried out. Material published not earlier than 2016, was chosen for the analysis. Most of the papers were published in journals with impact-factor not lower than 3.Results. After analyzing the information received, it was concluded that none of the technologies can be used independently. Inertial sensors possess high accuracy, but over time, the measurement error increases. There-fore, the sensors need to regular correction. Indoor-positioning based on geomagnetism is hampered by interference that can be induced by the operation of magnetic resonance imaging scanners and X-ray equipment, which are usually used in medical facilities. Active magnetometry does not allow to keep track of moving objects due to specific of hardware used. Ultrasound-based positioning can be complicated by ultrasonography apparatuses interference. Using an audible sound creates noise pollution and exerts a negative impact on patient’s health. Also, acoustic technologies are unable to provide a secure communication channel for data exchange.Conclusion. It is recommended to combine the reviewed positioning technologies with other technologies in order to correct the indicated disadvantages.